Kewenangan Pemerintah Daerah Dalam Memberantas Mafia Akomodasi Di Provinsi Bali - Sanjiwani, Putri Kusuma; Pujani, Luh Putu Kerti (Jurnal Ilmiah Pariwisata, 2020)
Term mafia is often heard in cases of international crimes involving money laundering businesses, selling drugs, human trafficking and others. Term mafia has entered into the tourism business in Bali Province. Mafia accommodation activities in Bali weaken the authority of Indonesia Republic with illegal activities. This research was conducted to find out how far practice of tourism accommodation mafia in Bali Province and authority of Provincial Government of Bali in eradicating the accommodation mafia in accordance with the division of government affairs both central, provincial and regional. The research method in this study uses the normative legal method, analyzing the problem based on rule of law, authority theory, tourism concept, tourism mafia concept and decentralization principle. Using legal analysis techniques and legal evaluation in determining the limitations of the authority of the Provincial Government in making policies. The results of this study indicate that the principle of freedom of contract is not a justification of the nominee agreement as the legal basis for accommodation mafia activities. There is a need to update regional regulations so that mafia activities can be ensnared by legal. Keywords: Mafia Tourism; International Crime; Tourism Law